HUMOR AND TRANSLATION: TO PROBLEM ADAPTATIONS HUMORIC TEXT TO FOREIGN LANGUAGE CULTURE - Yazichenko Olga Alekseyevna (Journal Park Publishing, 2024)
The article discusses ways of expressing the comic in novel by I. Ilf and E. Petrov “12 chairs” and ways of conveying humor as the most culturally and situationally specific type of comic in the translation of the novel into German.
Keywords: Humor, translation, culture, adaptation, translation transformation.